2011
DOI: 10.1158/1535-7163.mct-10-0809
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Mitotic Catastrophe on Abrogation of the G2 DNA Damage Checkpoint by UCN-01

Abstract: Genotoxic stress such as ionizing radiation halts entry into mitosis by activation of the G 2 DNA damage checkpoint. The CHK1 inhibitor 7-hydroxystaurosporine (UCN-01) can bypass the checkpoint and induce unscheduled mitosis in irradiated cells. Precisely, how cells behave following checkpoint abrogation remains to be defined. In this study, we tracked the fates of individual cells after checkpoint abrogation, focusing in particular on whether they undergo mitotic catastrophe. Surprisingly, while a subset of U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…3E). Furthermore, linearity between the S-G 2 duration and mitotic duration implies a causal connection between the interphase state and subsequent mitotic state, providing an explanation to previous work that implicates CHK1i in activating the spindle assembly checkpoint (16).…”
Section: Delayed S Progression Is a Denominator Of Cytotoxicity Regasupporting
confidence: 64%
“…3E). Furthermore, linearity between the S-G 2 duration and mitotic duration implies a causal connection between the interphase state and subsequent mitotic state, providing an explanation to previous work that implicates CHK1i in activating the spindle assembly checkpoint (16).…”
Section: Delayed S Progression Is a Denominator Of Cytotoxicity Regasupporting
confidence: 64%
“…IR treatment followed by checkpoint abrogation in other cell lines, including H1299, HCT116, U2OS, induced significantly less mitotic catastrophe than HeLa cells (4). However, we found that monastrol was also able to sensitize H1299 cells after checkpoint abrogation (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Previously, we have used long-term time-lapse microscopy to track the fates of individual cells after the ionizing radiation (IR)-mediated G 2 DNA damage checkpoint is abrogated with the CHK1 inhibitor UCN-01 (4). We found that the extent of mitotic cell death is closely related to the duration of mitosis.…”
Section: Introductionmentioning
confidence: 99%
“…Individual colonies were isolated and propagated in the absence of puromycin. HeLa cells (7) or H1299, HCT116, or U2OS cells (19) stably expressing histone H2B-GFP were used for live cell imaging. The same approach was used to generate Hep3B cells expressing histone H2B-GFP.…”
Section: Methodsmentioning
confidence: 99%